Hemodynamic changes in patients with extracorporeal membrane oxygenation (ECMO) demonstrated by contrast-enhanced CT examinations - implications for image acquisition technique. (April 2017) - Lambert, Lukas; Grus, Tomas; Balik, Martin; Fichtl, Jaromir; Kavan, Jan; Belohlavek, Jan
Extracorporeal membrane oxygenation (ECMO) is an established tool for respiratory and circulatory support. In computed tomography, altered hemodynamics in ECMO patients requires special considerations and handling in contrast injection and its timing. In this article, we demonstrate changes in hemodynamics in ECMO patients captured on contrast-enhanced CT examinations and pitfalls in strategies for contrast injection in relation to the ECMO flow, cardiac function and the placement of ECMO cannulas. Contrast-enhanced CT of patients with ECMO requires prior knowledge of the ECMO cannulas, central venous lines, changes of hemodynamics induced by low cardiac output and the influence of adjustment of ECMO on blood flow in order to optimize injection of the contrast material and timing of the scan. Special considerations include temporary reduction of the ECMO flow, selection of the injection site and increasing volume or flow rate of the contrast material.